Adherence to a long-term progressive resistance training program, combining supervised and home-based exercise for breast cancer patients during adjuvant treatment. (4th May 2019) - Lund, Linnea Waldorff; Ammitzbøll, Gunn; Hansen, Dorte Gilså; Andersen, Elisabeth Anne Wreford; Dalton, Susanne Oksbjerg
Abstract: Background: The purpose of the study was to examine adherence and identify patient- and treatment-related factors associated with adherence to a 20-week combined supervised and home-based progressive resistance training program in women treated for breast cancer. Methodology: The study population consisted of the intervention group in a randomized clinical trial examining the effect of resistance exercise on lymphoedema prevention ( n  = 82). The full program lasted 50 weeks, with an initial 20 weeks combined supervised and home-based exercise followed by 30 weeks self-administered exercise. Information about attendance rates (supervised exercise) and exercise dairies (home-based exercise) in the first 20 weeks was available for 74 and 62 participants, respectively. Adherence was measured as numbers of exercise sessions performed divided by expected number of exercise sessions with >2/3 categorized as high adherence. Age-adjusted odds ratios (OR) were used to assess the associations between patient- and treatment-related factors with adherence. Results: The number of participants with high adherence to supervised exercise decreased in the late period (from week 11 onward) compared to the early period (65% vs. 48%) whereas the proportion of participants with high adherence to home-based exercise remained close to 55%. The most prominent factor associated with high adherence to supervised exercise was neoadjuvant chemotherapy [OR 7.09; 95% confidence interval (CI), 1.12–44.62]. For home-based exercise, lower adherence was seen in obese participants (OR 0.16; 95% CI, 0.04–0.65) and in participants with average or below average lower body muscle strength at baseline (OR 0.12; 95% CI, 0.03–0.46). Conclusion: The results of this study offer valuable information on factors associated with adherence to a program of supervised and home-based exercise. Interventions may be adapted to ensure higher adherence rates through supportive efforts targeted to women who are obese, have low muscle strength and who receive no or adjuvant chemotherapy (as opposed to neoadjuvant chemotherapy) during exercise.